Beyond Our Means? Household Savings and Debt in Australia - Cassells, R.; Duncan, Alan; Kelly, S.; Ong, Rachel (Bankwest Curtin Economics Centre, CBS, Curtin University, 2015)
The ability of both households and governments to increase savings and manage debt has been an ongoing policy issue in Australia and throughout the world. Debt can be a good thing if it encourages real asset growth beyond that of interest repayments, as long as it does not interfere with other important economic activity. Beyond our Means is the second report in the Bankwest Curtin Economics Centre’s Focus on the States series. It brings new evidence to a national policy issue that impacts upon individuals, households and Australian States and Territories. Patterns of household savings and debt are explored over time and the issue of government debt examined. Australian government debt is low when compared to other OECD countries – ranked 21 out of 25. However, the trajectory of government net debt in the post-GFC period has been exponential, particularly in relation to government revenue, increasing from 15.2% to 54.4% in just over five years. This can become a burden to the Australian economy, increasing the risk of creditor downgrading and limiting the ability of governments to govern. Instead of servicing the Australian people, governments can end up spending more resources servicing debt.